Minimally Invasive Sinus Augmentation: A Systematic Review - Sirinirund, Benyapha; Rodriguez Betancourt, Amanda B.; Scaini, Riccardo; Wu, Yu‐Chang; Chan, Hsun‐Liang (Clinical implant dentistry and related research, 2025)
ABSTRACT Aim Technology improvement and a better understanding of sinus anatomy and wound healing in the past decade have allowed the development of minimally invasive surgical techniques. This systematic review focused on identifying and describing these techniques for vertical and lateral sinus augmentation (VSA and LSA). Materials and Methods Electronic and hand search were conducted to screen the literature published from January 2003 to May 2024. The selected studies had to include detailed techniques for minimally invasive SA. Data extraction included the study types, sample size, technique/instrument details, and outcome measurements. Results A total of 36 articles (27 VSA, 8 LSA with an additional 1 article included both procedures) with 2732 sinus augmentation met the inclusion criteria. Minimally invasive VSA includes the use of modified rotary instruments with stopper, balloon, hydraulic pressure, digital planning, endoscope, and operating microscope. These techniques aim for conservative flap reflection, precise sinus window preparation, and/or controlled sinus membrane elevation. Most of the selected studies (n = 15) did not report the incidence of sinus membrane perforation. Conclusion Within the limitations of this review, minimally invasive VSA and LSA achieved sufficient sinus augmentation and implant success with the potential advantages of reduced surgical complications and morbidity. Comparative studies with defined outcomes are encouraged to further validate these useful minimally invasive techniques for SA.